LENGTH-WEIGHT RELATIONSHIPS AND CONDITION FACTORS OF FISHES IN THE SOKH RIVER (Scientific journal of the Fergana State University, 2026)
The length-weight relationships (LWR) and condition factor of 14 fish species from the Sokh River were analyzed. The results indicated that 3 species exhibited isometric growth (b=3), 1 species (Triplophysa strauchii) showed negative allometric growth (b3). When the species' condition was assessed using Fulton's condition factor (K), the K value was found to be below 1 for Hemiculter leucisculus, Triplophysa daryoae, and Triplophysa strauchii. Conversely, it was observed to be higher than 1 for Carassius gibelio, Cottus spinulosus, Leuciscus squaliusculus, and Rhodeus ocellatus. The mean relative condition factor (Kn) for all species was 100.51±10.075.